Aneurysm of Upper Limb Arteries in Children: Report of Five Cases - Ildar Nurmeev; Dmitry Osipov; Bruce Okoye (Case Reports in Medicine)
Background. Arterial aneurysm in children is rare. Aim. To present the description of case series of successful surgical treatment of upper limb aneurysms in children. The case series included 2 boys and 3 girls, with median age 3.3 years. One of them was a newborn with a true brachial artery aneurysm. Aneurysms were in the brachial (n = 3) and radial (n = 2) arteries. Two patients had idiopathic aneurysms. Two cases were associated with connective tissue dysplasia syndrome. One patient had a history of trauma. In 4 of 5 cases, there was a true aneurysm and in one a pseudoaneurysm. Diagnosis was carried out in all cases by using ultrasound, with arteriography in one case. All 5 children were operated on. Resection of the aneurysm and restoration of arterial patency was performed in 4 of 5 cases (ligation of the radial artery near the aneurysm in 1 case, aneurysm resection with end-to-end anastomosis in 1 case, resection with PTFE graft implantation in 1 case, and resection with implantation of an autovenous graft in 2 cases. Complications. Dysfunction and thrombosis of the PTFE graft required reoperation using an autovenous graft. Conclusion. Despite the rarity of the disease, timely and adequate surgical treatment of aneurysms of the arteries of the upper extremities in children is possible successfully in a specialized hospital.